Axillary hyperhidrosis treated with alcoholic solution of aluminium chloride hexahydrate. Issue 6130 (8th July 1978) - Scholes, K T; Crow, K D; Ellis, J P; Harman, R R; Saihan, E M
Abstract : Sixty-five patients with axillary hyperhidrosis took part in a trial of treatment with a solution of 20% aluminium chloride hexahydrate in absolute alcohol, applied topically each night for a week and then whenever the patient thought it necessary. Excellent control of sweating was achieved in 64 patients, and occlusion of the area was found to be unnecessary. No troublesome side effects were reported. The results of this study indicate that 20% aluminium chloride hexahydrate in absolute alcohol is the treatment of first choice for patients with axillary hyperhidrosis.